Further simulation testing in CoopMAC-U for underwater acoustic sensor networks - Muhammad Syirajuddin S.; Nurul Hidayati; Rieke Adriati Wijayanti; Ahmad Wilda Yulianto; Dianthy Marya (Politeknik Negeri Malang, 2023)
In order for underwater wireless sensor networks to communicate more efficiently, MAC protocols are needed to control the use of acoustic channels. With the high propagation delay and the limited bandwidth available on the acoustic channel, a specially designed MAC protocol is needed for UWASN (Underwater Acoustic Sensor Networks). In this research, the adaptation of Cooperative MAC for underwater (CoopMAC-U) will be further studied to test the protocol performance. In the previous research, CoopMAC-U was simulated yet the fairness of the transmission was not simulated and tested. In this research, CoopMAC-U will be studied further and improved. The simulation result shows that the Improved CoopMAC-U protocol produces better-normalized throughput than the initial version of CoopMAC-U. The protocol is also proven that it is backward compatible between conventional mode and cooperative mode. For offered load greater than 0.2, both the initial version of CoopMAC-U and the Improved CoopMAC-U result in stagnant normalized throughputs but the improved ones double the value of the initial version.